CD4+CD25+CD127 regulatory cells play multiple roles in maintaining HIV-1 p24 production in patients on long-term treatment: HIV-1 p24-producing cells and suppression of anti-HIV immunity. (August 2015) - Jiao, Yan-Mei; Liu, Cui-e; Luo, Li-Jing; Zhu, Wei-Jun; Zhang, Tong; Zhang, Li-Guo; Su, Li-Shan; Li, Hong-Jun; Wu, Hao
Highlights: Depletion of regulatory T (Treg) cells may reduce HIV p24-producing cells and increase HIV-specific cytolytic T lymphocytes (CTL). Summary: Background: A major question when attempting to eradicate and treat HIV-1 infection is how to reactivate latent proviruses. Stimulating HIV-1-specific cytolytic T lymphocytes (CTL) has been shown to facilitate the elimination of the latent viral reservoir after viral reactivation. Regulatory T (Treg) cells are known to be capable of lowering both HIV-specific immunoreactions and general immune activation during HIV-1 infection. It was hypothesized that the depletion of Treg cells could increase the HIV-1-specific cytolytic T lymphocyte response and reactivate HIV-1 p24 production. Methods: Treg cells were isolated by isolation kit according to the surface marker of Treg cells. Real-time PCR method was used to quantify HIV-1 DNA. P24 antigens in the cell culture supernatant was done by ELISA. Cells activation and HIV specific HIV-1 CD8+ T cells were analyses using a FACSCalibur flow cytometer and CELLQUEST software. Results: This study included both HIV-infected patients who were antiviral treatment-naïve and patients with sustained viral responses to antiretroviral therapy (ART) for 1 or 5 years. It was found that the HIV-DNA levels in Treg cells were approximately 10-fold higher than those in non-Treg CD4+ cells and that the depletion of Treg cells could enhance the frequency of HIV-1-specific CTL and immune activation after 5 years of effective ART. Conclusions: CD4+CD25+CD127 regulatory cells play multiple roles in maintaining HIV-1 p24 production in long-term ART patients. Treg cells may be a target for eliminating the latent HIV reservoir after effective long-term ART.